2000
DOI: 10.1302/0301-620x.82b1.0820068
|View full text |Cite
|
Sign up to set email alerts
|

The medial approach for operative release of post-traumatic contracture of the elbow

Abstract: We treated post-traumatic contracture of the elbow in 13 consecutive patients (14 elbows) by operative release. Through a single medial approach, the posterior oblique bundle of the medial collateral ligament was resected, followed by posterior and anterior capsulectomies. An additional lateral release through a separate incision was required in only four elbows. The results were assessed at a mean interval of 57 months after operation.Before surgery active extension lacked 43° which improved to 17° after oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…We used the medial approach to release the ulnar nerve in our patient because, when flexion is limited to 90°prior to elbow release, ulnar neuritis frequently develops as patients regain flexion, which may limit further flexion following release of an elbow contracture 20 . The medial approach is also helpful in addressing any fibrous contracture of the posterior oblique ligament of the medial collateral ligament 7,8 ; this approach was helpful in addressing the contracture found close to the hyperostotic lesion in our patient. It is notable that proximal release of the flexor-pronator muscle facilitated the approach to the anterior capsule and Z-plasty was effective in overcoming the long-standing muscle contracture.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We used the medial approach to release the ulnar nerve in our patient because, when flexion is limited to 90°prior to elbow release, ulnar neuritis frequently develops as patients regain flexion, which may limit further flexion following release of an elbow contracture 20 . The medial approach is also helpful in addressing any fibrous contracture of the posterior oblique ligament of the medial collateral ligament 7,8 ; this approach was helpful in addressing the contracture found close to the hyperostotic lesion in our patient. It is notable that proximal release of the flexor-pronator muscle facilitated the approach to the anterior capsule and Z-plasty was effective in overcoming the long-standing muscle contracture.…”
Section: Discussionmentioning
confidence: 75%
“…The procedure was performed through a medial approach to the elbow 7,8 . The ulnar nerve was identified and mobilized.…”
Section: Case Reportmentioning
confidence: 99%
“…Wada et al [17] stated the benefits of the medial exposure and they found several advantages over the lateral approach. According to Wada et al [17], pathological changes in the posterior oblique bundle of the medial collateral ligament, and anterior and posterior aspects of the elbow joint, can be seen via one medial incision.…”
Section: Discussionmentioning
confidence: 99%
“…According to Wada et al [17], pathological changes in the posterior oblique bundle of the medial collateral ligament, and anterior and posterior aspects of the elbow joint, can be seen via one medial incision. This incision allows a complete soft-tissue release and excision of loose bodies at the olecranon and coronoid fossae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation